The microbiome alterations of supragingival plaque among adolescents using clear aligners: a metagenomic sequencing analysis - Chunlin Wang; Chao Zhang; Shan He; Qiuyu Wang; Hai Gao (Progress in Orthodontics)
Abstract Background White spot lesions (WSLs) may develop in adolescents undergoing clear aligner (CA) therapy with poor oral hygiene. The specific effects of CAs on the microbial composition and functional characteristics of supragingival plaques remain unclear. The present study investigated the shift in the supragingival microbial community induced by CAs in adolescents through metagenomic technology. Methods Fifteen adolescents (12–15 years old) with Invisalign appliances were recruited. Supragingival plaque specimens were obtained twice, before treatment (T1) and three months after treatment (T2). All the bacterial plaque specimens were analyzed for microbial communities and functions using metagenomic analyses. Results A total of 2,840,242,722 reads disclosed 180 phyla, 3,975 genera, and 16,497 microbiome species. During the first three months, the microbial community was relatively stable. The genus level revealed a higher relative abundance of Capnocytophaga, Neisseria, and Arachnia in the T2 period. Furthermore, the functional analysis suggested that the relative abundances of folate biosynthesis, biotin metabolism and biofilm formation-vibrio cholerae were increased in the T2 period compared to the T1 period. Finally, virulence factor analysis demonstrated that the relative abundance of genes associated with type IV pili (VF0082) and polar flagella (VF0473) was higher in the T2 period than in the T1 period. Conclusion In adolescents undergoing CA therapy with poor plaque control, caries progresses quickly within three months and noticeable WSLs develop on the tooth surface. Although the microbial community remained relatively steady and CA therapy did not cause significant changes in the overall functional gene composition in the first three months, virulence factors, including type IV pili and flagella, were more abundant and actively contributed to microorganism adhesion and biofilm formation.